1995
DOI: 10.1002/jnr.490420113
|View full text |Cite
|
Sign up to set email alerts
|

GM1 ganglioside rescues substantia nigra pars compacta neurons and increases dopamine synthesis in residual nigrostriatal dopaminergic neurons in MPTP‐treated mice

Abstract: GM1 ganglioside has been shown to stimulate recovery of the damaged dopamine system under a number of different circumstances. In addition to rescue of damaged dopamine neurons, the present study assessed the ability of GM1 to enhance the synthesis of dopamine in remaining nigrostriatal neurons following 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) exposure. There was a significantly greater accumulation of L-dopa 30 min after aromatic amino acid decarboxylase inhibition with NSD-1015 (100 mg/kg) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“….are second to no other class of biomolecules in the capacity of information coding using Box 1. Major functions of GM1 ganglioside Modulation of ion transport Na + /K + -ATPase antiporter [25] Ca 2+ influx via T type channel [28] Ca 2+ influx via TRPC5 channel [42] Ca 2+ efflux via plasma membrane Ca 2+ -ATPase (PMCA) [128,129] Na + /Ca 2+ exchange in nuclear membrane [130] Ca 2+ transfer from nucleoplasm to ER lumen [52] Neuronal differentiation Induction of ectopic neurites in gangliosidoses [61,62] Promotion of axonogenesis via sialidase and enhanced Ca 2+ influx [35,69,73] GM1 crosslinking activates TRPC5 Ca 2+ channels and neuritogenesis [42] Exogenous GM1 activates neuritogenesis nonspecifically [66][67][68] Neurotrophin modulation and neuroprotection Endogenous GM1 promotion of NGF activity via association with TrkA [86,131] Endogenous GM1 promotion of BDNF activity via association with TrkB [89] Endogenous promotion of GDNF activity via association with GFRa1/Ret [90] Exogenous promotion of neurotrophic activities [83,84,132,133] Neuroprotection by semisynthetic GM1 analogs (LIGA) [80,82] Roles in neurological disorders Spinal cord injury; GM1 benefit to subgroup of patients [134,135] PD: GM1 benefit in animal models [93][94][95] PD: GM1 benefit in clinical trials [97,98] PD: GM1 deficit as risk factor [90,100] PD: GM1 prevents aggregation of a-synuclein [101,102]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“….are second to no other class of biomolecules in the capacity of information coding using Box 1. Major functions of GM1 ganglioside Modulation of ion transport Na + /K + -ATPase antiporter [25] Ca 2+ influx via T type channel [28] Ca 2+ influx via TRPC5 channel [42] Ca 2+ efflux via plasma membrane Ca 2+ -ATPase (PMCA) [128,129] Na + /Ca 2+ exchange in nuclear membrane [130] Ca 2+ transfer from nucleoplasm to ER lumen [52] Neuronal differentiation Induction of ectopic neurites in gangliosidoses [61,62] Promotion of axonogenesis via sialidase and enhanced Ca 2+ influx [35,69,73] GM1 crosslinking activates TRPC5 Ca 2+ channels and neuritogenesis [42] Exogenous GM1 activates neuritogenesis nonspecifically [66][67][68] Neurotrophin modulation and neuroprotection Endogenous GM1 promotion of NGF activity via association with TrkA [86,131] Endogenous GM1 promotion of BDNF activity via association with TrkB [89] Endogenous promotion of GDNF activity via association with GFRa1/Ret [90] Exogenous promotion of neurotrophic activities [83,84,132,133] Neuroprotection by semisynthetic GM1 analogs (LIGA) [80,82] Roles in neurological disorders Spinal cord injury; GM1 benefit to subgroup of patients [134,135] PD: GM1 benefit in animal models [93][94][95] PD: GM1 benefit in clinical trials [97,98] PD: GM1 deficit as risk factor [90,100] PD: GM1 prevents aggregation of a-synuclein [101,102]…”
Section: Discussionmentioning
confidence: 99%
“…(For a description of several such trials and GM1 relevance, see the supplementary material online.) PD has drawn interest in regard to GM1 therapy based on promising preclinical results showing partial restoration of depleted striatal dopamine and nigrostriatal neuron recovery in MPTP-treated mice [93,94] and primates [95]. LIGA20 proved superior to GM1 in the murine model and was shown to have the advantage of oral bioavailability [96].…”
Section: Gm1 In Neurological Disordersmentioning
confidence: 98%
“…Treatment with GM1 following a number of different types of central nervous system lesions in experimental animals [9][10][11][12][13][14] has resulted in significant biochemical and behavioral recovery and pretreatment with GM1 inhibits damage resulting from a variety of neurotoxic exposures [15][16][17]. GM1 administration has been effective in ameliorating neurochemical and behavioral alterations in murine and non-human primate models of PD [13,[18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…We previously suggested that the symptomatic effect from GM1 in PD may relate to functional improvement in residual dopaminergic neurons, a conclusion supported by data showing enhanced dopamine synthesis in residual dopamine neurons in a mouse model of Parkinsonism following GM1 treatment 17 . In Phase II, ES subjects maintained some of the initial benefit of GM1 treatment and DS subjects showed benefit after switching to GM1 use and both treatment groups fared better than the Comparison subjects.…”
Section: Discussionmentioning
confidence: 77%
“…GM1 is highly expressed in the adult brain 4 where it modulates Ca 2+ homeostasis 5 and signal transduction, may promote lysosomal integrity 6 and influence mitochondrial function 7, 8 . In a variety of preclinical studies, administration of GM1 following different types of lesions resulted in significant biochemical and behavioral recovery 9-15 , with results particularly impressive in animal models of PD 1614171819202122 .…”
Section: Introductionmentioning
confidence: 99%